Effect of Al substitution on the magnetocaloric properties of Ni-Co-Mn-Sn multifunctional alloys. (April 2020) - Huang, L.; Cong, D.Y.; Ren, Y.; Wei, K.X.; Wang, Y.D.
Abstract: Ni-Mn-based metamagnetic shape memory alloys have been extensively studied due to their multifunctional properties including magnetocaloric effect (MCE), magnetoresistance effect, and magnetic-field-induced strain. However, the large intrinsic thermal hysteresis of these alloys sets a limit on further development for practical applications. Here, with a few atomic percent Al substitution, we greatly reduced the thermal hysteresis and transformation temperature interval while maintaining the large magnetization difference (Δ M ) between austenite and martensite. The simultaneous achievement of a large Δ M and low thermal hysteresis leads to a remarkable enhancement in MCE upon Al substitution, and a maximum magnetic entropy change of 31.6 J/kg K is achieved under a field of 5 T in Ni39 Co11 Mn40 Sn8 Al2 . Furthermore, our in situ high-energy X-ray diffraction experiments show that the Ni39 Co11 Mn40 Sn8 Al2 has good geometric compatibility between austenite and martensite, which accounts for the reduced thermal hysteresis in this alloy. This study is instructive for the development of high-performance magnetocaloric materials in the metamagnetic shape memory alloys. Highlights: The thermal hysteresis and transformation temperature interval were greatly reduced with Al substitution. The simultaneous achievement of a large magnetization difference and low thermal hysteresis. A large magnetic entropy change of 31.6 J/kg K under 5 T is achieved. Good geometric compatibility was disclosed by in situ high-energy X-ray diffraction technique.